Mental Disorders in Postpartum Period and Lactation: A Literature Review - Sadowska, Aleksandra; Welkier, Aleksandra; Sobiński, Adam; Kwaśniewska, Paula; Śliwa-Tytko, Patrycja; Miśkiewicz, Joanna; Dudek, Aleksandra; Pietrusińska, Patrycja; Moder, Jakub; Dziewierz, Anna (Quality in Sport, 2026)
Traditionally, postpartum mental problems have been characterized as major depressive disorder, obsessive-compulsive disorder, bipolar disorder, postpartum psychosis, and postpartum blues. The difficult postpartum phase is characterized by major changes in one’s physical, biological, social, and emotional makeup. This period necessitates significant interpersonal and personal adjustment, especially for primigravida women. A wide range of emotions are typical during pregnancy and the postpartum phase, ranging from anticipation, fulfillment, and excitement to feelings of anxiety, confusion, frustration, guilt, and sadness. This may cause the mother’s psychological condition to deteriorate. Misdiagnosis and inadequate treatment of prenatal mental illnesses are common. Both the mother and the child may have long-term effects from postpartum mental health disorders.The postpartum psychological state might become so severe that hospitalization is required. Furthermore, this conditions might have a negative impact on mother-infant connection and attachment. Early diagnosis and starting the treatment of postpartum psychiatric disorder is important, which can result in faster and quicker recovery. When the disease is mild or in its early stages, non-pharmacological treatment methods like psychotherapy, psychoeducation, and social and familial support might be beneficial. When the condition is more serious, medication is used. However, women should be mindful of the risks and benefits of using psychoactive medications during lactation, even though pharmacological treatment is more effective. Numerous factors, such as the mother’s medication dosage, the time and frequency of dosing, the mother’s drug metabolism rate, and the infant’s drug metabolism, influence how much drug an infant is exposed to.